The use of morphostructural analysis and IR spectrometry for diagnosis of the brain tumors - G. T. Maslova; J. I. Buloichik; A. P. Zajogin; A. S. Mavrichev; L. A. Derzhavets; A. S. Trubetskaya; A. V. Titova (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The morphology and IR absorption spectra of dried drops of the blood plasma from patients with brain tumors of different grades have been studied. The structural peculiarities of these drops have been revealed. The possibilities to use the structural features of dried drops and of their IR absorption spectra as a source of additional information facilitating correct diagnosis have been assessed. The developed methods enable to control the appointed treatment and to elucidate a dynamics of the developing pathology.